Analysis of a model for waterborne diseases with Allee effect on bacteria - Capone, Florinda; Carfora, Maria Francesca; De Luca, Roberta; Torcicollo, Isabella (Nonlinear Analysis: Modelling and Control, 2020)
A limitation of current modeling studies in waterborne diseases (one of the leading causes of death worldwide) is that the intrinsic dynamics of the pathogens is poorly addressed, leading to incomplete, and often, inadequate understanding of the pathogen evolution and its impact on disease transmission and spread. To overcome these limitations, in this paper, we consider an ODEs model with bacterial growth inducing Allee effect. We adopt an adequate functional response to significantly express the shape of indirect transmission. The existence and stability of biologically meaningful equilibria is investigated through a detailed discussion of both backward and Hopf bifurcations. The sensitivity analysis of the basic reproduction number is performed. Numerical simulations confirming the obtained results in two different scenarios are shown.
Keywords: waterborne disease; Allee effect; stability; ODEs system